Caries prevalence and enamel defects in 5- and 10-year-old children with cleft lip and/or palate: A case-control study. (17th February 2016) - Sundell, Anna Lena; Nilsson, Anna-Karin; Ullbro, Christer; Twetman, Svante; Marcusson, Agneta
Abstract: Objective. To determine the prevalence of dental caries and enamel defects in 5- and 10-year-old Swedish children with cleft lip and/or palate (CL(P)) in comparison to non-cleft controls. Materials and methods. The study group consisted of 139 children with CL(P) (80 subjects aged 5 years and 59 aged 10 years) and 313 age-matched non-cleft controls. All children were examined by one of two calibrated examiners. Caries was scored according to the International Caries Detection and Assessment System (ICDAS-II) and enamel defects as presence and frequency of hypoplasia and hypomineralization. Results. The caries prevalence among the 5-year-old CL(P) children and the non-cleft controls was 36% and 18%, respectively (p < 0.05). The CL(P) children had higher caries frequency (initial and cavitated lesions) in the primary dentition than their controls (1.2 vs 0.9; p < 0.05). A significantly higher prevalence of enamel defects was found in CL(P) children of both age groups and anterior permanent teeth were most commonly affected. Conclusions. Preschool children with cleft lip and/or palate seem to have more caries in the primary dentition than age-matched non-cleft controls. Enamel defects were more common in CL(P) children in both age groups.